2019
DOI: 10.1002/celc.201900174
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effect of Hydrogen Peroxide in the Electrochemical Treatment of Phenolic Pollutants using a BDD Anode

Abstract: Phenolic pollutants are recalcitrant substances that cannot be removed from wastewater using the current treatments. In this study, degradation of phenolic pollutants was studied on the basis of the application of hydrogen peroxide during the electrooxidation process using BDD as anode (EO−H2O2 coupled process). The process was optimized using 4‐chlorophenol (4‐CP) as model compound and later an emerging pollutant, Nonylphenol Ethoxylate‐10 (NP10EO), was degraded using the optimized experimental conditions fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…For instance, Brillas and co-workers [53] successfully demonstrated this application in their study of the degradation of monoazo, diazo, and triazo dyes using an electrochemical setup consisting of a carbon-ploytetrafluoroethylene (PTFE) air-diffusion cathode and a boron doped diamond anode (BDD). Carbon-PTFE has been used widely as a cathode for the two-electron reduction of oxygen forming H2O2 [54][55][56], while BDD has been extensively studied as an inactive anode for the direct production of heterogeneous HO • [57][58][59][60][61]. It was found that dye degradation occurred to both heterogeneous HO • created at the BDD anode and homogeneous HO • produced by the electro-Fenton process, where H2O2, produced at the carbon-PTFE cathode, reacted with added Fe 2+ .…”
Section: Hydrogen Peroxide (H2o2)mentioning
confidence: 99%
“…For instance, Brillas and co-workers [53] successfully demonstrated this application in their study of the degradation of monoazo, diazo, and triazo dyes using an electrochemical setup consisting of a carbon-ploytetrafluoroethylene (PTFE) air-diffusion cathode and a boron doped diamond anode (BDD). Carbon-PTFE has been used widely as a cathode for the two-electron reduction of oxygen forming H2O2 [54][55][56], while BDD has been extensively studied as an inactive anode for the direct production of heterogeneous HO • [57][58][59][60][61]. It was found that dye degradation occurred to both heterogeneous HO • created at the BDD anode and homogeneous HO • produced by the electro-Fenton process, where H2O2, produced at the carbon-PTFE cathode, reacted with added Fe 2+ .…”
Section: Hydrogen Peroxide (H2o2)mentioning
confidence: 99%
“…Electrooxidation can be improved by coupling with other oxidation processes. In the case of electrooxidation of nonylphenol ethoxylate-10 with boron-doped diamond anode with addition of hydrogen peroxide, greater efficiency is achieved as showed by Barrera et al (2019). Even a small amount of hydrogen peroxide (0.25 mL 30% v/w per 1.1 L of solution) acts as a promoter for the formation of hydroxyl radicals in the solution by removing 94.3% of pollutant in 375 min of treatment.…”
Section: Electrochemical Degradationmentioning
confidence: 99%
“…The effect of the pH of the aqueous solution was evaluated and two values were selected, 6.2 and 2.7 respectively. Another parameter that has influence in the electrooxidation process is the current density and two values were evaluated 22.2 and 16.6 mA cm -2 [24,25].…”
Section: Electrooxidationmentioning
confidence: 99%